Crop yield in India in relation to EI-Nino - CHOWDHURY, A. (MAUSAM, 1995)
ABSTRACT. Association between the EI- Nino events in the Pacific Ocean and the crop yields in India has been examined. Five districts,viz. Churu, Gwalior, Rewa, Palamau and Bankura located on the normal monsoon trough zone and cultivating altogether different, mostly rainfed crops, were selected for the study. Crop and seasonal rainfall data from 1951-88 were utilised in the analysis. The results indicate that the EI-Nino phenomenon does not exert much influence on the kharif. In wave models with cons crops in India.